On the fate of the secondary white dwarf in double-degenerate double-detonation Type Ia supernovae: II. 3D synthetic observables - Pollin, Joshua; Sim, S A; Pakmor, R; Callan, F P; Collins, C E; Shingles, L J; Röpke, Friedrich; Srivastav, S (Monthly notices of the Royal Astronomical Society, 2024)
A leading model for Type Ia supernovae involves the double-detonation of a sub-Chandrasekhar mass white dwarf. Double-detonations arise when a surface helium shell detonation generates shockwaves that trigger a core detonation; this mechanism may be triggered via accretion or during the merger of binaries. Most previous double-detonation simulations only included the primary white dwarf; however, the fate of the secondary has significant observational consequences. Recently, hydrodynamic simulations accounted for the companion in double-degenerate double-detonation mergers. In the merger of a 1.05 M$_{\odot }$ primary white dwarf and 0.7 M$_{\odot }$ secondary white dwarf, the primary consistently detonates while the fate of the secondary remains uncertain. We consider two versions of this scenario, one in which the secondary survives and another in which it detonates. We present the first 3D radiative transfer calculations for these models and show that the synthetic observables for both models are similar and match properties of the peculiar 02es-like subclass of Type Ia supernovae. Our calculations show angle dependencies sensitive to the companion’s fate, and we can obtain a closer spectroscopic match to normal Type Ia supernovae when the secondary detonates and the effects of helium detonation ash are minimized. The asymmetry in the width-luminosity relationship is comparable to previous double-detonation models, but the overall spread is increased with a secondary detonation. The secondary detonation has a meaningful impact on all synthetic observables; however, multidimensional nebular phase calculations are needed to support or rule out either model as a likely explanation for Type Ia supernovae.